Inattentiveness to Warnings and Precautions on Prescription Drug Labels among Malaysian Adult Patients: The Influence of Polypharmacy - Chan, Huan-Keat; Rahim, Siti Nadiah Abd; Kassim, Mohd Shainol Azmar; Chew, Beng-Hoong; Suan, Mohd Azri Mohd (Journal of Pharmacy Practice and Community Medicine)
Background: Cautionary information on prescription drug labels is crucial to ensure safe administration. The current study examined patients’ attentiveness to warnings and precautions on drug labels in a Malaysian public hospital. Methods: Five labels of the most commonly prescribed medications in the hospital were shown to 208 adult patients. Using face-to-face interviews, participants were asked to interpret the information on the labels. Results: The majority (78.4%) of the participants did not attempt to interpret the warnings and precautions of at least one label. Inattentiveness to such information was also found to be associated with polypharmacy, which was defined as taking five or more prescription medications (adjusted odds ratio: 8.57; 95% confidence interval: 1.44, 50.96; p=0.02). Conclusion: This study confirms the lack of awareness of drug safety among the Malaysian population in general, highlighting the need for improving patient education and revising the labeling format.
Keywords: Drug labeling; Malaysia; Public hospitals; Polypharmacy; Prescription drugs